Pengembangan Sistem Informasi Distribusi Budidaya Ikan Lele (Studi Kasus di Kecamatan Karangploso Kabupaten Malang) - Muhammad Rizqian Noor; Adam Hendra Brata; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Karangploso District has a lot of culinary potentials, catfish food is one of them which often available in many restaurants within the district. Due to the long distribution chain, the price of catfish can be relatively high. The first chain comes from catfish farmers, next is the first supplier, move along to the second supplier, the fourth is the market traders, and the fifth goes to the restaurant. Based on this problem, a system is developed to ease the catfish distribution chain. The system development will be used by distributors, restaurants, and catfish farmers. There are also drivers as well to pick up the catfish harvests and eventually deliver it. Within this system, catfish farmers can make a fine schedule towards the harvest times, restaurants can manage the market demands, and distributors can monitor the daily distribution deals. This study uses the waterfall method. This system is developed into two platforms, the first is a website used by distributors and the second is the android which will be used by catfish farmers, restaurants and drivers. The test result with the whitebox method produced a 100% valid score. For the validation testing, the writer used the blackbox method and the result is 100% valid. Meanwhile, the writer used two types of browsers for websites and two types of android versions for compatibility testing. The result is also 100% valid.